Assessment of the predictors of smoking cessation of adult smokers in Mendez, Cavite - Angeles, Rain L.​; Panopio, Jeanne Pauline G.​; Pornillos, Britley Anne H.​; Ruamero Jr., Edwin C.​ (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2018.)
Tobacco smoking causes several health problems such as cancer, cardiovascular diseases, diabetes, pneumonia, and chronic obstructive pulmonary diseases. Thus, smoking cessation programs are being introduced to communities. Smoking cessation is a form of behavioral change which can be described by the Transtheoretical Model of Behavioral Change (TTM). It suggests that behavior change involves progress through five stages: precontemplation, contemplation, preparation, action, and maintenance. For this study, only the first three stages were included since only the intent to quit was desired. This study aimed to associate significant predictors with the willingness of a smoker to undergo smoking cessation. The respondents were classified according to the stage of change they are in. The study also described the smokers in terms of their sociodemographic profiles and nicotine dependence. Among the probable predictors studied were government mediated interventions, family and friends, cost, and health motivational factors, nicotine dependence, process of change, and decisional balance. This study employed a cross-sectional research design. This study included 369 respondents from 12 barangays in Mendez, Cavite. Data was collected using the seven-part questionnaire and analyzed using ordinal logistic regression. Among the respondents across the stages of change, 51% were found to be precontemplators, 21% contemplators, and 28% preparers. Of the initial independent variables, the three determined to be significant to the three stages of change for the population are Decisional Balance, Health Motivation, and Policy Awareness. The odd ratios of being in the preparation stages are 2.83, 1.42 and 0.38, respectively.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2018.
Keywords: Smoking cessation